Draft Annual Plan 1980-81 Part-I Outline Union Territory of Delhi - Planning Commission (Planning Commission, 1979)
Annual Plan 1980-81 against the anticipated expenditure of Rs 10 lakhs in the current financial years The main objectives of the programmes of this Sector are provision of facilities for specialised courses of study in Art Education such as line art, fine art, sculpture, Volopcierit of library and acquisition of specimen of art.
Union Territory of Delhi, Planning Department